2018
DOI: 10.3390/app8091540
|View full text |Cite
|
Sign up to set email alerts
|

Remote-Sensing Image Encryption Algorithm Using the Advanced Encryption Standard

Abstract: With the increasing use of multimedia in communications, the content security of remote-sensing images attracts much attention in both the academia and industry. The Advanced Encryption Standard (AES) is a famous symmetric cryptosystem. A symmetric remote-sensing image encryption algorithm using AES is presented. Firstly, to reduce the encryption times, the sender groups 16 pixel values together, and converts them into big integers; secondly, the sender encrypts big integers with AES and the chaotic system; fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Huang et al [11] suggested a simple chaotic for encryption of color image which is relied on plaintext related permutation and diffusion for more safty and efficacy. Zhang and Wang [12] introduced the AES remote sensing image encryption algorithm. At first, for time reduction of encryption, the source gathers the values of 16 pixels altogether to form big integers; secondly, the source ciphers big integers by AES and chaotic map; lastly, the ciphered image is resulted from the encrypted big integers.…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al [11] suggested a simple chaotic for encryption of color image which is relied on plaintext related permutation and diffusion for more safty and efficacy. Zhang and Wang [12] introduced the AES remote sensing image encryption algorithm. At first, for time reduction of encryption, the source gathers the values of 16 pixels altogether to form big integers; secondly, the source ciphers big integers by AES and chaotic map; lastly, the ciphered image is resulted from the encrypted big integers.…”
Section: Related Workmentioning
confidence: 99%
“…[44] Ciphertext image − 0.0039 − 0.0196 0.0027 Ref. [55] Ciphertext image − 0.0047 0.0025 0.0014 Ref. [56] Ciphertext image 0.0019 0.0038 − 0.0019…”
Section: Classical Types Of Attacksmentioning
confidence: 99%
“…Differential attack [32] is an efficient method to use pairs of plain-images related by a constant difference and compare the difference of the corresponding cipher-image for statistical patterns in their distribution. Usually attackers make a tiny change in the plain-image and use the encryption algorithm to encrypt the image before and after any changes.…”
Section: Differential Attackmentioning
confidence: 99%